Peran Humas dalam Pelaksanaan Branding Terminal Tipe A Tirtonadi - Syerli Alifa Rahmadani; Rahmat Wisudawanto; Esfandani Peni Indreswari (Institut Nalanda, 2025)
Public Relations (PR) has a strategic role in building a positive image of an institution. This study aims to analyze the role of public relations of Tirtonadi Type A Terminal in the implementation of branding. The research method used is a qualitative approach with data collection techniques through interviews, observation, and documentation. The results showed that the public relations of Tirtonadi Type A Terminal carried out four main roles, namely as a communicator, relationship builder, back-up management, and good image maker. However, there are still challenges in the consistency of communication strategies and the image of the terminal in the community. SWOT analysis shows the need for improvement in social media management and public services to improve the terminal's image.